2010
DOI: 10.1002/ejic.201000792
|View full text |Cite
|
Sign up to set email alerts
|

Titanium(IV)–Salan Catalysts for Asymmetric Sulfoxidation with Hydrogen Peroxide

Abstract: We report the synthesis and the solution and solid-phase characterization of several titanium(IV)–salan complexes. The structures of the ligands H2sal(R,R-chan), H2ovan(S,S-chan), and H6pyr(R,R-chan)4+·4Cl–·H2O were determined by single-crystal X-ray diffraction and their main features are compared and discussed. Single crystals suitable for X-ray diffraction studies were also obtained for [Ti4{sal(R,R-chan)}4(μ-O)4] and showed a tetranuclear core bearing μ-oxo bridges between the titanium atoms and the ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Taking into account their much higher intrinsic stability and much lower susceptibility toward hydrolysis, several publications were released either with characterization of metal complexes [153,[160][161][162][163][164] or using these very versatile ligands to prepare suitable complexes to prepare metal-based catalytic systems [163,[165][166][167][168][169][170][171][172].…”
Section: Metal Ion-salen Complexesmentioning
confidence: 99%
“…Taking into account their much higher intrinsic stability and much lower susceptibility toward hydrolysis, several publications were released either with characterization of metal complexes [153,[160][161][162][163][164] or using these very versatile ligands to prepare suitable complexes to prepare metal-based catalytic systems [163,[165][166][167][168][169][170][171][172].…”
Section: Metal Ion-salen Complexesmentioning
confidence: 99%
“…Reduction of the CN bond to a CN bond yields a tetrahydro derivative of salen (salan; Fig. ) . The presence of an amine backbone (instead of an imine) results in a more flexible structure, which is also more resistant than the salen CN bond to hydrolysis .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported that the enantioselective oxidation of various sulfides with 'green' 30% aqueous hydrogen peroxide could be performed in the presence of catalytic amounts of titanium–salan complexes (0.2–1.0 mol%); the asymmetric induction was generated in a tandem stereoconvergent asymmetric oxidation/kinetic resolution process . Pessoa and Correia with co‐workers synthesized a series of related titanium catalysts with 1,2‐cyclohexanediamine and 1,2‐diphenylethylenediamine as chiral moieties and reported the catalytic oxidation of thioanisole, with moderate enantiomeric excess (ee) values . Further studies revealed that titanium–salan catalyst 1 had an optimal structure only for the highly enantioselective oxidation of bulky aryl benzyl sulfides, while the oxidation of smaller sulfides (such as thioanisole derivatives and alkyl phenyl sulfides) proceeded with lower chemo‐ and enantioselectivity …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] On the other hand, several titanium-based catalyst systems appeared in the last few years, some of them surpassing the Kagan-Modena systems in terms of chemo-and stereoselectivity, as well as in ease of handling and sustainability, especially those relying on H 2 O 2 as the oxidant. [10][11][12][13][14][15][16][17][18] Previously, we reported that the enantioselective oxidation of various sulfides with 'green' 30% aqueous hydrogen peroxide could be performed in the presence of catalytic amounts of titaniumsalan complexes (0.2-1.0 mol%); the asymmetric induction was generated in a tandem stereoconvergent asymmetric oxidation/ kinetic resolution process. [16] Pessoa and Correia with co-workers synthesized a series of related titanium catalysts with 1,2-cyclohexanediamine and 1,2-diphenylethylenediamine as chiral moieties and reported the catalytic oxidation of thioanisole, with moderate enantiomeric excess (ee) values.…”
Section: Introductionmentioning
confidence: 99%